Peningkatan Keterampilan Digital Guru Bahasa Inggris melalui Pelatihan Microsoft 365 for Education di Kabupaten Takalar - Novia, Lely; Asfah, Indrawaty; Mustikawati, Yunitari; Noni, Nurdin; Burhamzah, Muftihaturrahmah (Abdimas Indonesian Journal, 2024)
The Training for Enhancing Digital Skills of English Teachers through Microsoft 365 for Education in Takalar Regency aims to improve teachers’ digital skills in utilizing technology for learning. The training materials include the use of various Microsoft 365 applications, such as Teams, Forms, OneDrive, Sway, and Stream, as well as Office Online applications like Word, PowerPoint, and Excel. Participants were allowed to learn and use these applications. In addition to improving instructors' digital proficiency, this training helped make learning more dynamic and interesting for pupils. In general, this program is anticipated to enhance Takalar Regency's educational standards, especially concerning technology-based learning.